Pentingnya Meningkatkan Kemampuan Berbahasa Inggris Para Mudabbirah di Pondok Pesantren - Muhammad Amin; Lalu Thohir; Mahyuni Mahyuni (Jurnal Gema Ngabdi, 2020)
Mudabbirah, an Arabic word which means ‘coach’ is part of an Islamic boarding school management. Different from any other personnel of school management, Mudabbirah are selected among students of the 11th grade. This element of management is usually based in each room where students live and is responsible for controlling the day-to-day activities of other students staying in the room. In addition to tasks such as ensuring discipline, mudabbirah is also given a responsibility to coach their juniors in learning foreign languages (in this particular school Arabic and English). Due to the important role this school element plays, this training was held in order to improve mudabbirah language mastery as well as their teaching methodology. The findings show that mudabbirah showed enthusiasm which is reflected by their attendance and activeness during the training. By doing so it is hoped that they can perform their duty better as a result of better developed language knowledge and skills in English and at the same time are skillful coach for their peers